2015
DOI: 10.1111/sbr.12127
|View full text |Cite
|
Sign up to set email alerts
|

Restless leg syndrome and associated factors in patients with paralytic poliomyelitis

Abstract: The aim of this study was to assess the presence of Restless Leg Syndrome (RLS) in patients with poliomyelitis, and associated factors. Forty-six patients with paralytic poliomyelitis who were followed-up in 2014 were included in the study. The RLS diagnosis was made according to the survey forms by International Restless Legs Syndrome Study Group. The RLS rating scale was used to rate the disease severity. The Pittsburgh sleep quality index (PSQI) was used to assess sleep quality. The Beck depression inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous studies (6, 7) have reported a higher prevalence for RLS in patients with MS than in the general public. The prevalence of RLS in the general public has been reported as 3% to 15% (8,9). Meanwhile, in MS patients, the incidence of RLS has been reported as 27% to 65% according to different articles (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (6, 7) have reported a higher prevalence for RLS in patients with MS than in the general public. The prevalence of RLS in the general public has been reported as 3% to 15% (8,9). Meanwhile, in MS patients, the incidence of RLS has been reported as 27% to 65% according to different articles (10,11).…”
Section: Introductionmentioning
confidence: 99%